Multilocus sequence typing of Dientamoeba fragilis identified a major clone with widespread geographical distribution - Caccio, Simone M.; Sannella, Anna Rosa; Bruno, Antonella; Stensvold, Christen R.; David, Erica Boarato [UNESP]; Guimaraes, Semiramis [UNESP]; Manuali, Elisabetta; Magistrali, Chiara; Mahdad, Karim; Beaman, Miles; Maserati, Roberta; Tosini, Fabio; et al. (Elsevier B.V., 2016)
The flagellated protozoan Dientamoeba fragilis is often detected in humans with gastrointestinal symptoms, but it is also commonly found in healthy subjects. As for other intestinal protozoa, the hypothesis that genetically dissimilar parasite isolates differ in their ability to cause symptoms has also been raised for D. fragilis. To date, only two D. fragilis genotypes (1 and 2) have been described, of which genotype 1 largely predominates worldwide. However, very few markers are available for genotyping studies and therefore the extent of genetic variation among isolates remains largely unknown. Here, we performed metagenomics experiments on two D. fragilis-positive stool samples, and identified a number of candidate markers based on sequence similarity to the phylogenetically related species Trichomonas vaginalis. Markers corresponding to structural genes and to genes encoding for proteases were selected for this study, and PCR experiments confirmed their belonging to the D. fragilis genome; two previously described markers (small subunit ribosomal DNA and large subunit of RNA polymerase II) were also included. Using this panel of markers, 111 isolates of human origin were genotyped, all of which, except one, belonged to genotype 1. These isolates had been collected at different times from symptomatic and asymptomatic persons of different age groups in Italy, Denmark, Brazil and Australia. By sequencing approximately 160 kb from 500 PCR products, a very low level of polymorphism was observed across all the investigated loci, suggesting the existence of a major clone of D. fragilis with a widespread geographical distribution. (C) 2016 Australian Society for Parasitology. Published by Elsevier Ltd. All rights reserved.
Keywords: Dientamoeba fragilis; Human; Genetic markers; Multilocus genotyping; Population structure